Iowa RBA, January 29, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for January 29, 1996. Highlights of the update include sightings of two first year Glaucous Gulls, a first year Thayer's Gull, Lesser Black-backed Gull and a Black-legged Kittiwake. Also included are handwritten notes for the next week's update with sightings of a Golden Eagle, an albino Blue Jay and a Pileated Woodpecker. Epson - sheet feed/flatbed